Effect of training cessation on muscular performance: A meta-analysis - Bosquet, L.; Berryman, N.; Dupuy, O.; Mekary, S.; Arvisais, D.; Bherer, D.; Mujika, I. (Scandinavian Journal of Medicine & Science in Sports, 2013)
The purpose of this study was to assess the effect of resistance training cessation on strength performance through a meta-analysis. Seven databases were searched from which 103 of 284 potential studies met inclusion criteria. Training status, sex, age, and the duration of training cessation were used as moderators. Standardized mean difference (SMD) in muscular performance was calculated and weighted by the inverse of variance to calculate an overall effect and its 95% confidence interval (CI). Results indicated a detrimental effect of resistance training cessation on all components of muscular performance: [submaximal strength; SMD (95% CI) = -0.62 (-0.80 to -0.45), P < 0.01], [maximal force; SMD (95% CI) = -0.46 (-0.54 to -0.37), P < 0.01], [maximal power; SMD (95% CI) = -0.20 (-0.28 to -0.13), P < 0.01]. A dose-response relationship between the amplitude of SMD and the duration of training cessation was identified. The effect of resistance training cessation was found to be larger in older people (> 65 years old). The effect was also larger in inactive people for maximal force and maximal power when compared with recreational athletes. Resistance training cessation decreases all components of muscular strength. The magnitude of the effect differs according to training status, age or the duration of training cessation.